The Impact of Tourism Management on Rural Community Welfare : A Case Study of Trans Patoa Village, South Bolaang Mongondow Regency - Surahmad Laya; Radia Hafid; Melizubaida Mahmud; Meyko Panigoro; Agil Bahsoan (International Journal of Economics and Management Research, 2025)
This study investigates the impact of tourism management on the welfare of rural communities, using Trans Patoa Village in South Bolaang Mongondow Regency as a case study. Despite the village's natural tourism potential, community welfare remains low due to limited skills and employment opportunities. A quantitative approach was employed, utilizing a simple linear regression model to analyze the relationship between tourism management and community welfare. Data were collected from 40 local tourism service providers through validated and reliable instruments. The results show a strong and significant positive relationship between tourism management and community welfare, with a standardized coefficient (Beta) of 0.721 and a p-value of 0.000. These findings indicate that effective, inclusive, and community-based tourism management can significantly enhance economic conditions, job opportunities, and quality of life in rural areas. This research highlights the strategic role of tourism in sustainable rural development and offers recommendations for stakeholders to strengthen tourism governance and community empowerment.